2020
DOI: 10.1038/s41598-020-64684-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment systemic inflammatory markers in patients with locally advanced rectal cancer following neoadjuvant chemoradiotherapy

Abstract: The aim of this study was to explore the most powerful systemic inflammation marker of survival in locally advanced rectal cancer (LARC) patients and construct prognostic nomograms. A total of 472 LARC patients undergoing neoadjuvant chemoradiotherapy (NCRT) and radical surgery from 2011 to 2015 were included. The optimal cutoff points for the systemic immune-inflammation index (SII); and neutrophil-to-lymphocyte (NLR), platelet-to-lymphocyte (PLR), and monocyte-to-lymphocyte (MLR) ratios were calculated and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 29 publications
1
39
0
1
Order By: Relevance
“…Patient inclusion criteria, treatment protocol and follow up were as described in our previous study. 23 Briefly, preoperative long-course radiation consisted of a total dose of 45 Gy to the pelvis. Concurrent chemotherapy was initiated on the first day of radiotherapy using one of two chemotherapeutic regimens: 5FU plus oxaliplatin (FOLFOX) or capecitabine plus oxaliplatin (CapeOX).…”
Section: Methodsmentioning
confidence: 99%
“…Patient inclusion criteria, treatment protocol and follow up were as described in our previous study. 23 Briefly, preoperative long-course radiation consisted of a total dose of 45 Gy to the pelvis. Concurrent chemotherapy was initiated on the first day of radiotherapy using one of two chemotherapeutic regimens: 5FU plus oxaliplatin (FOLFOX) or capecitabine plus oxaliplatin (CapeOX).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, an increasing number of studies have demonstrated the value of inflammatory response biomarkers as predictive markers for prognosis in cancers. It has been shown that the neutrophil-tolymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune inflammation index (SII) can predict the prognosis in various types of cancers (7)(8)(9). The systemic inflammation response index (SIRI) is a new systemic inflammatory response biomarker based on peripheral blood cells counts, and it was demonstrated to be effective in predicting the prognosis of esophagogastric junction adenocarcinoma (10), esophageal cancer (11) and cervical cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Xie et al 32 demonstrated that the high SII was independently correlated with unfavorable OS in patients with metastatic CRC. However, two clinical studies 33,34 investigating the prognostic significance of the SII in CRC patients receiving neoadjuvant chemoradiotherapy showed that the SII was not an independent predictor for OS or DFS. In addition, a recent study 7 with 408 CRC patients reported that SII was not associated with OS or DFS in multivariate Cox regression analyses.…”
Section: Discussionmentioning
confidence: 99%